The Role of Social Workers in Handling Comorbid Elderly Through the Jiwong Jiga Application to Prevent the Covid-19 - Pamungkas, Andri; Chandrani, Ane Nur; Maulana, Khasfi; Rizkotul Amalia, Siti Aisyah; Alifah, Siti Alifah (Sultan Journal of Social Sciences and Humanities, 2024)
Social work is a profession that encourages social change in society by solving problems related to human relations which is a professional activity in helping individuals and society. Social workers are also based on the body of knowledge, body of skills, and body of vavalues. Social workers also provide services to people of all ages, from newborns to the elderly. In the discussion of this research, the role of social workers in dealing with comorbid elderly through the Jiwong Jiga application to suppress the Covid 19 virus in Purwokerto Wetan. This social worker treats comorbid elderly, which means that the elderly experience comorbid conditions with weakened immune systems and are more difficult to fight off infections. By using the jiwong jiga application, which means siji wong siji guard (one person, one guard) with the program carried out, one person is sick, then one person takes care of the sick in an effort to minimize the spread of the covid-19 virus and can see the percentage of the rise and fall of the spread of the covid-19 virus in Purwokerto Wetan.